Operational Analysis Of Murabahah On Gold Savings Products On Deposit Fund Profits At Pegadaian Syariah (Case Study Of PT. Pegadaian Syariah UPS Karimata Situbondo) - Mufidatul Himmah M, E; Dila Lailatul Qodariyah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study analyzes the operational implementation of the murabahah contract in the Gold Savings product at Pegadaian Syariah UPS Karimata Situbondo and its impact on entrusted fund profits. Murabahah, as a sale and purchase contract with an agreed profit margin, has been applied in Gold Savings, where customers purchase gold gradually using a buy-deposit system. This research employs a case study approach with data collection methods including observation, interviews, and documentation. The findings indicate that the Gold Savings product at Pegadaian Syariah utilizes the murabahah contract and a buy-deposit system, allowing customers to store gold balances before printing or reselling them. The benefits of this product include the ease of sharia-compliant gold investment, transaction flexibility, and long-term profit potential. However, challenges such as rising gold prices and the need for public education about this product remain. This study provides insights into the role of the murabahah contract in increasing public interest in gold investment at Pegadaian Syariah.